Deforestation and its causal factors in Sinaloa, Mexico - Monjardín-Armenta, Sergio A.; Pacheco-Angulo, Carlos E.; Plata-Rocha, Wenseslao; Corrales-Barraza, Gabriela (Instituto de Ecología, A.C., 2017)
The objective of this research was to study deforestation and its causes in the state of Sinaloa, Mexico. Using mapping of land use and vegetation in 1993 and 2011 at a scale of 1: 250 000, deforestation was estimated through a technique of detecting changes, and then characterized by consulting experts. Finally, a matrix of change was applied to analyze the losses, gains and transitions and to corroborate cartographically the results obtained by the experts and the detection of changes. The results indicate a deforestation of 126.50 km2/year and an average annual rate of 0.41%. The consultation of experts determined that the main causes of these processes are agricultural expansion and extension of infrastructure, with impacts of 49.40% and 18.8%, respectively. The matrix of change showed that the particular category of rainforest lost 2374.19 km2, on the contrary, seasonal agriculture also increased by 3326.62 km2 and human settlements increased from 191.51 km2 to 623.28 km2.